Business associativity as an alternative for the competitive success of the SMEs in Costa Rica - Salas León , Carlos (2022)
Due to the insufficient documented knowledge about the factors that affect business associativity and how this can positively affect the competitive position of SMEs in Costa Rica, there is a great need to learn more about its potential to contribute towards such groups´ competitiveness and sustainability. The research method takes in consideration associative projects that are geographically located in Costa Rica, for which a mixed research scheme (qualitative-quantitative) was followed, with a review of existing secondary sources and obtaining primary information through the statistic method of proportions for finite populations. This research contributes to the state of knowledge about the motives that influence SMEs in Costa Rica to associate and the conditions contributing whit these associative groups to become successful. The competitive success of associative projects depends on a series of factors that involve both intrinsic aspects (those proper and internal to the SMEs associations, such as the group competitive advantages achieved by the association) as well as extrinsic aspects (those external to the associations). The trust relationships, the leadership of the members, and their perceived benefits, emerge as the main factors identified.